Phytochemical Composition, Antioxidant and Xanthine Oxidase Inhibitory Activities of Amaranthus cruentus L. and Amaranthus hybridus L. Extracts - Jeanne F. Millogo; Odile G. Nacoulma; Adama Hilou; Fernand W. Nana (MDPI AG, 2012)
This paper describes a preliminary assessment of the nutraceutical value of Amaranthus cruentus (A. cruentus) and Amaranthus hybridus (A. hybridus), two food plant species found in Burkina Faso. Hydroacetonic (HAE), methanolic (ME), and aqueous extracts (AE) from the aerial parts were screened for in vitro antioxidant and xanthine oxidase inhibitory activities. Phytochemical analyses revealed the presence of polyphenols, tannins, flavonoids, steroids, terpenoids, saponins and betalains. Hydroacetonic extracts have shown the most diversity for secondary metabolites. The TLC analyses of flavonoids from HAE extracts showed the presence of rutin and other unidentified compounds. The phenolic compound contents of the HAE, ME and AE extracts were determined using the Folin-Ciocalteu method and ranged from 7.55 to 10.18 mg Gallic acid equivalent GAE/100 mg. Tannins, flavonoids, and flavonols ranged from 2.83 to 10.17 mg tannic acid equivalent (TAE)/100 mg, 0.37 to 7.06 mg quercetin equivalent (QE) /100 mg, and 0.09 to 1.31 mg QE/100 mg, respectively. The betacyanin contents were 40.42 and 6.35 mg Amaranthin Equivalent/100 g aerial parts (dry weight) in A. cruentus and A. hybridus, respectively. Free-radical scavenging activity expressed as IC50 (DPPH method) and iron reducing power (FRAP method) ranged from 56 to 423 µg/mL and from 2.26 to 2.56 mmol AAE/g, respectively. Xanthine oxidase inhibitory activities of extracts of A. cruentus and A. hybridus were 3.18% and 38.22%, respectively. The A. hybridus extract showed the best antioxidant and xanthine oxidase inhibition activities. The results indicated that the phytochemical contents of the two species justify their traditional uses as nutraceutical food plants.